2012
DOI: 10.1007/s11628-012-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Airline website loyalty formation and the moderating effects of gender and education

Abstract: The objective of this study is to analyse the moderating effects of gender and education on users' loyalty to the website of an airline. We provide a tested model for greater understanding the effects of gender and education on the loyalty of experienced users in utilitarian purchasers of airline's website. The results reveal that website quality, esatisfaction, e-trust and affective e-loyalty are antecedents of conative e-loyalty in loyalty relationships between passengers and airline websites, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
0
13
1
2
Order By: Relevance
“…Hasil penelitian Ryu et.,al (2012), menyatakan bahwa kepuasan konsumen terjadi pada nilai yang diterima oleh konsumen tersebut. Kepuasan yang muncul pada diri konsumen menimbulkan loyalitas sehingga menguntungkan bagi perusahaan (Forgas-Coll; Palau-Saumell; Sanchez-Garcia; Fandos- Roig, 2013;Pantouvakis;Lymperopoulos, 2008).…”
Section: Kajian Teoriunclassified
“…Hasil penelitian Ryu et.,al (2012), menyatakan bahwa kepuasan konsumen terjadi pada nilai yang diterima oleh konsumen tersebut. Kepuasan yang muncul pada diri konsumen menimbulkan loyalitas sehingga menguntungkan bagi perusahaan (Forgas-Coll; Palau-Saumell; Sanchez-Garcia; Fandos- Roig, 2013;Pantouvakis;Lymperopoulos, 2008).…”
Section: Kajian Teoriunclassified
“…This model proved to be a reliable and valid service quality measurement instrument for the business tourism industry (Swart and Roodt 2011a), while partial mediation through satisfaction is also evident (Chang and Polonsky 2012;Swart and Roodt 2011b). An investigation of market segmentation variables have become synonymous in tourism industry related research (Forgas-Coll et al 2013;Kim et al 2009a;Li et al 2013;Rid et al 2014). However, none of the identified studies indicated a moderating effect in the prediction of Retention through a SQSC.…”
mentioning
confidence: 99%
“…For this, affective e-loyalty, e-trust, e-satisfaction and a positive offline perceived value should be provided in the first place. Studying on moderating effects of gender and education on loyalty towards an airline website, Forgas-Coll et al [8] stated that website quality, esatisfaction, e-trust and affective e-loyalty were the antecedent of conative e-loyalty and emphasized that university level education affected the loyalty positively. Elkhani, Soltani and Jamshidi [5] studied airline websites from the perspective of customers and put an emphasis on the importance of gaining new customers and making existing customers loyal.…”
Section: Travel Airlines and Websitesmentioning
confidence: 99%